The mystery of the stolen diamonds - Adler, David A.; Natti, Susanna (New York : Puffin Books, 2010)
A fifth-grader with a photographic memory and her friend Eric help solve the mystery of the stolen diamonds.
Ages 7 up.
Keywords: Theft -- Juvenile fiction; Detective and mystery fiction